1997
DOI: 10.1177/026565909701300103
|View full text |Cite
|
Sign up to set email alerts
|

'Teacher talk' with children with language disorders: four case studies I

Abstract: In part I of this paper the general characteristics of 'teacher talk' and that of four language unit teachers are examined, and the effect of different move types on the degree of spontaneous speech exhibited by their pupils is shown. Qualitative differences in overall style of interaction among the four teachers were found which appeared to reflect differences in pedagogic goals and individual beliefs regarding the importance of conversation rather than the degree of control they exerted over subsequent pupil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Sadler and Mogford‐Bevan's (1997a,b) results suggest that teachers, like other adults, may be relatively unaware of their language behaviours, and that even positive beliefs about features of effective talk does not mean that these are used in practice. It would not be safe to assume that teachers can always use facilitating interaction styles, nor that those who believe they do so are accurate, nor that changes can be easily made on the basis of receiving advice.…”
Section: The Lts Templatementioning
confidence: 98%
See 1 more Smart Citation
“…Sadler and Mogford‐Bevan's (1997a,b) results suggest that teachers, like other adults, may be relatively unaware of their language behaviours, and that even positive beliefs about features of effective talk does not mean that these are used in practice. It would not be safe to assume that teachers can always use facilitating interaction styles, nor that those who believe they do so are accurate, nor that changes can be easily made on the basis of receiving advice.…”
Section: The Lts Templatementioning
confidence: 98%
“…However, research on teacher talk suggests that it is not always adapted in the recommended way. Sturm and Nelson (1997) noted more teacher ‘mazes’ (non‐fluencies and revisions) in end‐primary compared to early‐primary classes in mainstream schools in the USA, and Sadler and Mogford‐Bevan (1997a,b) also observed that some teachers of language‐impaired children in language units in England used high numbers of reformulations of their own utterances, which were not always successful in solving communication problems. These unit teachers talked more to talkative children, and controlled the classroom talk using open and closed questions.…”
Section: The Lts Templatementioning
confidence: 99%
“…In IRE/F discourse contexts, however, children with specific speech and language difficulties run the risk of becoming passive and lacking engagement in their learning . Minimal participation may lead to reduced opportunities for language learning because topicrelated exchanges are shortened and trouble sources may remain unresolved (Sadler and Mogford-Bevan 1997).…”
Section: Introductionmentioning
confidence: 99%
“…and among their peers (Fujiki, Brinton, Isaacson, & Summers, 2001). Children with LI showed conversational turns that were shorter than those of their non-impaired peers in a special needs classroom (Sadler & Mogford-Bevan, 1997) and during nonstructured preschool activities (Rice et al, 1991). There is no strong evidence to suggest that children with LI initiate less in the classroom, but there is evidence of social reticence or withdrawal (Fujiki et al, 2001;Fujiki et al, 1999), and their short responses may be indicative of such social reticence or lack of classroom participation.…”
mentioning
confidence: 99%
“…Turn taking has been the focus of classroom discourse studies in an effort to identify (a) the three-part classroom discourse structure of initiation-response-feedback (IRF ;Cazden, 1988Cazden, , 2001Lemke, 1990;Mehan, 1979;Orsolini & Pontecorvo, 1992), (b) evidence of teacher control of talk (Sadler & Mogford-Bevan, 1997), and (c) patterns of student participation (Rice et al, 1991). Turn taking has been examined in children with learning disabilities (Dollaghan, 1987;Donahue, 1984) and among first and second language learners (Lerner, 1995), and it is crucial to understand for children with LI within the classroom.…”
mentioning
confidence: 99%